Exciton-acoustic phonon coupling revealed by resonant excitation of single perovskite nanocrystals - Yan Lv (Nature Portfolio, 2021)
In order to develop perovskite nanocrystals as a single-photon source, there is a need to understand the complex exciton photo-physics. Here, the authors employ resonant and near-resonant excitation technique to study single CsPbI3 nanocrystal that allows them to probe the continuous and size-quantised acoustic-phonon modes.